Strategy Analysis Of Train Journey Tourism Packages In Improving Hotel Occupancy During The Covid-19 Pandemic At Amanjiwo Resort, Magelang Regency, Central Java - Lisnawati, Ni Wayan; Pramesti, Dinar Sukma; Mulia, Victor Bangun (Politeknik Internasional Bali, 2024)
The Train Journey tour package is the latest innovation launched by Amanjiwo Resort during the Covid-19 pandemic to help increase hotel occupancy. The aim of this research is to analyze the strategies implemented in the Train Journey package and the efforts made to increase hotel occupancy during the Covid-19 pandemic at Amanjiwo Resort. The research method is qualitative, with data collection through interviews. The study uses the marketing mix theory (7P). The results reveal that the strategies implemented are as follows: from the product aspect, Amanjiwo Resort plans to add 2-3 Train Journey trips per month after the Covid-19 pandemic; from the price aspect, the price of the Train Journey trip remains in line with the room type; from the place aspect, Amanjiwo Resort focuses on the Jakarta-Yogyakarta route by increasing the number of trips; from the promotion aspect, Amanjiwo Resort selects media for promotion carefully; from the people aspect, the staff serving the Train Journey guests consists of 6 people, with a guest capacity of 8-12 pax; from the process aspect, the Train Journey is inspired by the Orient Express and then modified; and from the physical evidence aspect, Amanjiwo Resort continues to utilize the facilities provided by PT KAI (Indonesian Railways). The development strategies that can be implemented to increase occupancy include: from the product aspect, Amanjiwo Resort does not need to add more train carriages, but can increase the number of Train Journey trips or combine it with other tour packages; from the price aspect, Amanjiwo Resort can increase the price of the Train Journey trip during certain periods; from the place aspect, Amanjiwo Resort can add a new route, namely Surabaya-Yogyakarta; from the promotion aspect, Amanjiwo Resort should target more travel agents; from the people aspect, Amanjiwo Resort should engage in discussions with guests regarding meal schedules; from the process aspect, Amanjiwo Resort needs to introduce the Train Journey trip to guests; and lastly, from the physical evidence aspect, Amanjiwo Resort should coordinate with PT KAI (Indonesian Railways) to select specific dates for additional Train Journey trips.